HUBUNGAN PENGETAHUAN IBU DAN PEKERJAAN IBU DENGAN PEMILIHAN KONTRASEPSI SUNTIK - Fahrini Yulidasari; Ardik Lahdimawan; Dian Rosadi (Lambung Mangkurat, 2015)
Abstract Indonesian is one of the developing countries with various kinds of issues which is population growth was too high and the problem of maternal mortality. One of ways government to keep pressing the rate of increase parity through family planning programs. Family planning programs in Indonesia be stagnant has marked with the increase family planning service where the number of family planning participants had just reach 57,9%. Family planning program in South Kalimantan on 2014 was not yet reached a target where the participants of family planning programs recorded 52,82% of the mother. This study is to analyze if there are relationship between the mother’s knowledge about contraceptive method and mother’s occupation with injection contraception selection in Paringin City, South Kalimantan. The study used analytic observasional method with cross sectional approach. The samples were taken as many as 50 people were considered representative of study sites. The instrument used was a questionnaire. Samples were taken by using purposive sampling technique. The primary data analysis research using by chi-square test. Based on the results, relationship between mother’s knowledge with injection contraception selection was not significant (p-value=0,180). However, there is a significant relationship between mother’s occupation with injection contraception selection (p=0,031, OR=4,455). If mother’s knowledge about methods of contraception getting better, the user of injection contraception will be increase. Occupation status will affect the economic status of the family. A family with high economic status is encouraged the formation of a large family. Therefore, it is necessary to further dissemination of the benefits and impacts of using the injection contraception selection that have an impact on increasing public knowledge. Keywords: knowledge, occupation, family planning program, injection contraception